2017
DOI: 10.3390/su9030420
|View full text |Cite
|
Sign up to set email alerts
|

Public Open Space Development for Elderly People by Using the DANP-V Model to Establish Continuous Improvement Strategies towards a Sustainable and Healthy Aging Society

Abstract: Abstract:With the global trend of population aging, how to integrate the health needs of elderly people into public open space (POS) development while taking into account public interest is a major challenge in the 21st century. Although the issues of elderly people's health and their POS needs are receiving increasing attention, research on continuous improvement strategies for POS for healthy aging societies is still limited. Hence, this study explored continuous improvement strategies thoroughly and systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 60 publications
1
73
0
Order By: Relevance
“…First, to explore the plausible influential relationships among all the considered criteria, the DEMATEL technique [33,34] is incorporated into the analytic network process (ANP) [35] method in MCDM. The DEMATEL method was proposed to evaluate complicated social problems assuming that all criteria have influences on each other, which has been successfully applied in identifying cause-effect influences for various applications, such as evaluating the improvement strategies of public open space for elderly people [36] and new technology [37]. The integration of DEMATEL and ANP may help adjust the dimensional weights in the classical ANP method, which also simplifies the design of questionnaire for collecting DMs' opinions [38].…”
Section: Multiple Criteria Decision-making (Mcdm) Methods In Financementioning
confidence: 99%
“…First, to explore the plausible influential relationships among all the considered criteria, the DEMATEL technique [33,34] is incorporated into the analytic network process (ANP) [35] method in MCDM. The DEMATEL method was proposed to evaluate complicated social problems assuming that all criteria have influences on each other, which has been successfully applied in identifying cause-effect influences for various applications, such as evaluating the improvement strategies of public open space for elderly people [36] and new technology [37]. The integration of DEMATEL and ANP may help adjust the dimensional weights in the classical ANP method, which also simplifies the design of questionnaire for collecting DMs' opinions [38].…”
Section: Multiple Criteria Decision-making (Mcdm) Methods In Financementioning
confidence: 99%
“…Finally, the study verified the effectiveness of the DDANPVM model through empirical analysis, and confirmed that the gap between various factors of several candidate products through the modified VIKOR method, providing references for decision-makers and consumers [17][18]. The combination of DANP and the modified VIKOR method [18][19][20][21][22] enables the identification of performance limitations, thereby prioritizing their improvement and promoting consumers' adoption of mobile health care. These results were concluded through quantitative analysis, which offered specific sustainable development planning advice.…”
Section: Research Content and Frameworkmentioning
confidence: 99%
“…Third, we recognized the cause-effect relationships between criteria and dimensions and confirmed the key influence factors and their IWs. The DEMATEL method can be used to construct an INRM and determine the IWs, preserving the relationships among dimensions and criteria in a universal model based on the basic concept of ANP, which has been termed DANP [17][18][19][20][21][22]. Finally, the study verified the effectiveness of the DDANPVM model through empirical analysis, and confirmed that the gap between various factors of several candidate products through the modified VIKOR method, providing references for decision-makers and consumers [17][18].…”
Section: Research Content and Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, society benefits from ensuring that elderly individuals receive necessary assistance in all aspects of their lives. One way to realize these benefits is to ensure that urban public spaces and facilities are suitable for the elderly [2][3][4][5]. Providing safe, inclusive, and accessible public spaces can help the elderly obtain a higher quality of life and better health conditions [6,7]; thus, the sustainable development of cities can be more easily achieved [8].…”
Section: Introductionmentioning
confidence: 99%